RSAS 4.6 summary - Bennett, Bruce W., 1952-; Fox, Daniel B. (Daniel Bryan), 1946-; Jones, Carl.; Painter, Lawrence S.; Schrader, John Y.; Weissler, Robert; Wilson, Barry, 1959-; Rand eBooks (Santa Monica, CA : RAND, 1992)
The RAND Strategy Assessment System (RSAS) is a global war gaming and analysis system that focuses on conflict, from major regional contingencies through strategic warfare. It has been developed to support balance assessment, contingency analysis, and military training. It is global because it includes order-of-battle data for most major countries worldwide. This Note summarizes the development status of RSAS 4.6, as released, describing each of its components and how they have been changed since RSAS 4.0. It describes known limitations of the RSAS and enhancements the authors feel ought to be made, as a reference point for RSAS applications and future development. Finally, it provides some basic information on how to use the RSAS, how it is designed to be used, and descriptions of RSAS inputs and outputs.
"A research publication from the RAND Strategy Assessment Center."
"Performed within the International Security and Defense Strategy Program of RAND's National Defense Research Institute"--Preface.
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Computer war games; War games -- Data processing; War -- Computer simulation; United States -- Defenses -- Computer simulation; Electronic books